2022
DOI: 10.3389/fpsyg.2022.868692
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Contract, Self-Efficacy, Job Stress, and Turnover Intention: A View of Job Demand-Control-Support Model

Abstract: The outbreak of Coronavirus disease 2019 (COVID-19) has caused enterprises to face more challenges, such as operational management, production and sales management, and human resource management, among other issues. In the context of the global knowledge economy, employees with high knowledge and skills have become an important source of corporate growth and breakthroughs. However, employees may intend to transfer to other companies due to the pressure of the external and internal environments, so the main top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 92 publications
(176 reference statements)
1
4
0
Order By: Relevance
“…A total of 553 responses were selected to be analysed. The findings proposed that higher SE resulted a strong negative effect on OS (Shao et al, 2022). The present study which had a sample of 89 also obtained similar results.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…A total of 553 responses were selected to be analysed. The findings proposed that higher SE resulted a strong negative effect on OS (Shao et al, 2022). The present study which had a sample of 89 also obtained similar results.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…The Job Demand-Control-Support (JDCS) model is a widely used model that focuses on relationships between work-related stresses and adverse outcomes in physiology (cardiovascular disease, sleepiness, and musculoskeletal complaints), psychology (burnout), and organization (job satisfaction, organizational commitment, and turnover intention) [ 28 , 29 , 30 , 31 ]. According to this model, job strain comes from the combined influence of two key aspects, job demands and job control [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research results have confirmed that employees' perceived insider status is negatively correlated with their turnover intention (Knapp et al, 2014). Employees' willingness to stay in the organization is largely influenced by their level of involvement in the organization and the extent to which the organization recognizes them (Shao et al, 2022). Compared with permanent employees, temporary workers have a lower sense of insider status and are more likely to leave their jobs because they worry about their future jobs and their low status among members (Arain et al, 2018;Liu X. et al, 2022).…”
Section: Perceived Insider Status and Turnover Intentionmentioning
confidence: 77%